Four new species of Tonnoira Enderlein (Diptera: Psychodidae: Psychodinae) from the Brazilian Atlantic forest - Santos, Claudiney Biral Dos; Curler, Gregory R. (Zootaxa, 2014)
Four species of Tonnoira from the Brazilian Atlantic forest are described and illustrated: Tonnoira brisolaii sp. nov, Tonnoira ferreirai sp. nov., Tonnoira andradei sp. nov. and Tonnoira galatiae sp. nov.